Resource Allocation for Uplink M2M Communication: A Game Theory Approach - Hashim, Safdar; Norsheila, Fisal; Rahat, Ullah; Wajahat, Maqbool; Faiz, Asraf; Zubair, Khalid; Adnan, Shahid Khan (2013)
Machine-to-Machine (M2M) communication in cellular network is the driver for the future Internet of Things (IoT). The main challenge of M2M communication is the possibility of huge traffic in the uplink network that can cause problem in the network. This paper considers the problem of resource allocation among machines connecting in uplink to different femto base stations (FBSs). Resource allocation problem is analyzed through both non-cooperative and cooperative game to maximize their data rate and minimize utilization of power. Numerical result shows that by adapting non-cooperative game, all machines are getting data rate as per Nash Equilibrium (NE) or either they can set their strategy to maximize their data rate selfishly. On the other hand for coalitional game theory approach machines who participate in game are getting fair resource allocations.